Pengembangan dan Implementasi Aplikasi Pengawasan Ternak Berbasis Android di Peternakan Bukit Aren Farm Majalengka - Faraj Faraj; Adian Fatchur Rochim; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2015)
Bukit Aren Farm located in Majalengka, West Java is a company specialized in the broiler of the agriculture industry, farming broiler performed in different places and every breeding cattle carried monitored by the supervisory staff. Every day, staf record information manually about the animal in the cage that data will be used as a performance evaluation of animal production. The livestock management personnel encountered problems when running calculations of the evaluation product and efficiency livestock because the calculation process can be done if the existing data stored carefully and systematically, in particular the data recorded cattle in significant quantities, it would require much time for staff supervision to determine the level of production performance. Application developed using waterfall method. The waterfall model is composed of: requirements, design, implementation, verification, maintenance. To begin the design steps required observations or interviews to determine the needs of the system under design. Applications developed using CodeIgniter framework, angularjs and ionic based architecture. Results of the project is the application mobile livestock monitoring data storage that can serve the number of deaths, data on the number quarantine of chicken, and the amount of data that then feed use these data will generate a data value prices and feed consumption levels of livestock mortality information for the evaluation process in the livestock in line with the business processes of Bukit Aren Farm. The application has been tested by using black box method and the results of these tests indicate that all functions in the system has been well running on the Android operating system from version 4.1.